2015
DOI: 10.18632/oncotarget.3670
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone-mediated regulation of lipocalin 2 through the Met/FAK pathway in liver cancer

Abstract: The thyroid hormone, 3,3′,5-triiodo-L-thyronine (T3), regulates cell growth, development and differentiation via interactions with thyroid hormone receptors (TR), but the mechanisms underlying T3-mediated modulation of cancer progression are currently unclear. Lipocalin 2 (LCN2), a tumor-associated protein, is overexpressed in a variety of cancer types. Oligonucleotide microarray, coupled with proteomic analysis, has revealed that LCN2 is positively regulated by T3/TR. However, the physiological role and pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…38,39 Abrogation of FAK with multiple modalities, including small interfering RNA, AdFAK-CD, and small molecule inhibitors, has been shown to decrease tumor migration and to increase survival. 44,45 Integrins bind to the β subunits of FAK and lead to FAK phosphorylation. Chen et al 43 demonstrated that the expression of FAK correlated with tumor stage and vascular invasion of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Abrogation of FAK with multiple modalities, including small interfering RNA, AdFAK-CD, and small molecule inhibitors, has been shown to decrease tumor migration and to increase survival. 44,45 Integrins bind to the β subunits of FAK and lead to FAK phosphorylation. Chen et al 43 demonstrated that the expression of FAK correlated with tumor stage and vascular invasion of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, administration of TH not only reduces the size of preneoplastic lesions in the livers of rats suffering with HCC, but suppresses the aberrant cellular growth via control the expression of cell cycle regulators, such as CDK2, Cyclin E, UHRF1, STMN1 mir-214 and BC200 lncRNA [7,[171][172][173][174]. Our recent studies further support the preventive effect of TH on hepatocarcinogenesis via activating autophagy [16,17], whereas TH/THR is reported to promote metastasis and chemoresistance through control the expressions of BSSP4, TRAIL, BCL2L11, LCN2, mir-21, and mir-130b [7,173,[175][176][177][178][179][180]. This characteristic of THs supports the double-edged sword effect of autophagy in cancer progression.…”
Section: Discussionsupporting
confidence: 65%
“…Significant links between the regulation of selective autophagy and liver complications associated with NAFLD and HCC have been reported, supporting the manipulation of this process as a potential therapeutic strategy for liver-related diseases. Apoptosis regulator TRAIL [175] Metastatic regulator BSSP4 [178] LCN2 [180] mir-130b [177] mir-21 [179] Autophagy in liver-related diseases…”
Section: The Th/thr Axis In Regulation Of Hepatic Autophagy the Autopmentioning
confidence: 99%
“…As it is known to us all, FAK was served as an upstream factor of AKT signaling [ 33 , 34 ], our finding may provide a new sight to Lasp1 function. Since the activation of FAK signaling is shown to be regulated by c-Met signaling [ 35 37 ], we also evaluated the phosphorylation of c-Met and Gab1 after either overexpressing or depleting Lasp1. No significant changes were observed ( Supplementary Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%